The inhibitory effect of sense of power on experiential sports consumption: the chain-mediated role of psychological distance and social orientation - Guo, Kai; Huang, Qian (Frontiers in Psychology, 2025)
IntroductionTo explore the internal driving mechanisms influencing consumers' preferences for experiential sports consumption, this study constructs a structural equation model with experiential sports consumption as the dependent variable and sense of power as the independent variable, integrating the Agentic–Communal Model of power perception. Psychological distance and social orientation are introduced as mediating variables.MethodsThis study utilized survey data from 1,062 Chinese sports consumers to empirically test the proposed structural equation model.ResultsThe analysis reveals the following findings: 1) Sense of power has a significant negative predictive effect on experiential sports consumption, with consumers perceiving lower sense of power more likely to choose experiential sports consumption; 2) Psychological distance mediates the relationship between sense of power and experiential sports consumption. Lower sense of power makes consumers feel a closer psychological distance, which in turn makes them more inclined to choose experiential sports consumption; 3) Social orientation also plays a mediating role in this process, with consumers perceiving lower sense of power more likely to seek social interaction to enhance their consumption experience through higher social orientation; 4) Psychological distance and social orientation jointly form a chain mediation effect between sense of power and experiential sports consumption. Lower sense of power shortens psychological distance, which in turn enhances social orientation, thus driving the choice of experiential sports consumption.DiscussionThe research findings not only expand the theoretical framework of the impact of sense of power on sports consumer behavior but also provide theoretical support for sports enterprises when developing differentiated marketing strategies, particularly in how to design personalized strategies based on consumers' perceived differences in sense of power.